The Influence of Zakat Literacy, Attitude, and Motivation on The Behavior of Profesional Zakat Payment in Jombang Regency - Aisyah Farah Dina; Shahrul Bin Mohammad Nasim; Mochammad Alfian Dwi Bhaihaqi (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2026)
This study aims to examine the influence of zakat literacy, attitude, and motivation on the behavior of professional zakat payment among the Muslim community in Jombang despite its high potential in Indonesia. Employing a quantitative approach with an questionnaire and analyzed using multiple linear regression with SPSS version 23. The findings reveal that zakat literacy and motivation have a positive and significant effect on professional zakat payment behavior. Conversely, attitude shows a negative and significant influence. Simultaneously, all three variables significantly affect the behavior of professional zakat payment, accounting for 32.3% of the behavioral variance. These results highlight the importance of integrative efforts encompassing cognitive, affective, and motivational dimensions to enhance zakat compliance. The study provides practical insights for zakat institutions in developing more effective educational programs and communication strategies to promote professional zakat.